RANCANG BANGUN SISTEM INFORMASI POINT OF SALE DENGAN FRAMEWORK CODEIGNITER PADA CV POWERSHOP - Lim, Maydianto; Ridho, Muhammat Rasid (Computer Science and Industrial Engineering, 2021)
CV POWERSHOP is a small startup CV company engaged in printers and computers. The problem that often occurs at CV POWERSHOP is managing inventory of goods. All of these activities are still carried out manually and are still not well controlled, it can be seen that there are still data items that do not match the stock records. Therefore, the author wants to provide a solution to CV POWERSHOP by creating a web-based application to manage inventory data for these items. In building this POS information system the author uses the UML system development methodology as a tool in the design stage, the programming language used to build the information system uses PHP (PHP Hypertext Pre-processor) and XAMPP as a database. Texteditor used to write program code using Sublime Text. With this inventory information system, it is hoped that the inventory management of goods will be more effective and efficient.